Anti-obesity effect of a traditional Chinese dietary habit—blending lard with vegetable oil while cooking. Issue 1 (December 2017) - Wang, Ji; Yan, Sisi; Xiao, Haisi; Zhou, Huijuan; Liu, Shuiping; Zeng, Yu; Liu, Biying; Li, Rongfang; Yuan, Zhihang; Wu, Jing; Yi, Jine; Razack, Yarou; et al.
Abstract Obesity, which is associated with dietary habits, has become a global social problem and causes many metabolic diseases. In China, both percentages of adult obesity and overweight are far lower compared to western countries. It was designed to increase the two levels of daily intake in human, namely 3.8% and 6.5%, which are recommendatory intake (25 g/d) and Chinese citizens' practical intake (41.4 g/d), respectively. The mice were respectively fed with feeds added with soybean oil, lard or the oil blended by both for 12 weeks. In the mice fed with diet containing 3.8% of the three oils or 6.5% blended oil, their body weight, body fat rate, cross-sectional area of adipocytes, adipogenesis and lipogenesis in adipose were decreased, whereas hydrolysis of triglyserides in adipose was increased. This study demonstrated that the oil mixture containing lard and soybean oil had a remarkable anti-obesity effect. It suggests that the traditional Chinese dietary habits using oils blended with lard and soybean oil, might be one of the factors of lower percentages of overweight and obesity in China, and that the increasing of dietary oil intake and the changing of its component resulted in the increasing of obesity rate in China over the past decades.